English Language Proficiency Development Among Primary School Students: Challenges and Solutions - Soliha, Imro Atus (MODELING: Jurnal Program Studi PGMI, 2023)
This research delves into the complexities of English la This research delves into the complexities of English language instruction at the primary school level in Probolinggo, where English proficiency is crucial in the global context. Despite the importance of English education, challenges persist, including a shortage of trained teachers and unique characteristics of primary education. Employing a qualitative approach, this study presents insights obtained through expert interviews, focus group discussions, and content analysis of relevant literature. The findings emphasize the need for engaging, interactive teaching materials that integrate various language skills and capture students' attention. Although the English language program has proven effective, challenges arise in classroom implementation due to resource constraints and teacher limitations. To address these challenges, greater involvement from schools and the community is sought. This research aims to inform strategies for enhancing English language instruction at the primary school level in Probolinggo. nguage instruction at the primary school level in Probolinggo, where English proficiency is crucial in the global context. Despite the importance of English education, challenges persist, including a shortage of trained teachers and unique characteristics of primary education. Employing a qualitative approach, this study presents insights obtained through expert interviews, focus group discussions, and content analysis of relevant literature. The findings emphasize the need for engaging, interactive teaching materials that integrate various language skills and capture students' attention. Although the English language program has proven effective, challenges arise in classroom implementation due to resource constraints and teacher limitations. To address these challenges, greater involvement from schools and the community is sought. This research aims to inform strategies for enhancing English language instruction at the primary school level in Probolinggo.